Financial development and the distribution of income in Latin America and the Caribbean - Gustavo Canavire-Bacarreza; Felix Rioja (Institute for the Study of Labor (IZA), 2008)
One of the central concerns in Latin America and the Caribbean (LAC) has been the reduction of poverty and inequality so prevalent in the continent. Using large world samples, the literature has found that financial development increases economic growth, increases the income of the poor, and reduces inequality. This paper studies the effects of financial development on the whole distribution of income in LAC. We find that the income of the poorest quintile has not been affected by expansion in the financial system. However, we do find that financial development has had a disproportionate positive effect on the incomes of the second, third and fourth quintiles. We also find some evidence for the Greenwood-Jovanovic (1991) hypothesis that this positive effect only begins after a country crosses a certain economic development threshold.
urn:nbn:de:101:1-20081126704
Keywords: O11; 330; Distribution of income; financial development; inequality; Einkommensverteilung; Soziale Ungleichheit; Finanzsektor; Entwicklungsstufe; Lateinamerika; Karibische Staaten